أثر تقدير الخطر الحتمي على اختبارات المراجعة- دراسة ميدانية - - زيود لطيف; سعيد عهد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدراسة إلى تحديد أثر تقدير الخطر الحتمي على اختبارات المراجعة, لذلك تم إجراء مسح ميداني باستخدام الاستبانة على عينة من المراجعين الذين استطاع الباحث التواصل معهم, حيث تم توزيع /56/ استبانة, تم استرجاع /34/ استبانة منها, وقد أظهرت نتائج تحليل البيانات أن هناك موافقة من قبل أفراد العينة المدروسة على وجود تأثير إيجابي طردي لتقدير الخطر الحتمي على اختبارات المراجعة. كما أظهرت النتائج بأنه من الممكن تقسيم مكونات الخطر الحتمي اعتماداً على نتائج التحليل العاملي إلى ثلاثة مكونات, كما يمكن تقسيم مكونات اختبارات المراجعة إلى مكونين أثنين, الأمر الذي سمح بدراسة أثر تقدير كل من مكونات الخطر الحتمي على مكونات اختبارات المراجعة. وجاءت النتائج لتظهر بأن تقدير العامل الأول للخطر الحتمي يؤثر ايجاباً على العامل الأول لاختبارات المراجعة, في حين لم يظهر له أي تأثير على العامل الثاني لاختبارات المراجعة. أما فيما يخص العامل الثاني للخطر الحتمي فقد تبين بأن تقديره يؤثر إيجاباً على العامل الأول لاختبارات المراجعة, في حين لم يظهر له أي تأثير على العامل الثاني لاختبارات المراجعة. وأخيراً أظهرت النتائج وجود تأثير عكسي لتقدير العامل الثالث للخطر الحتمي على كل من العاملين الأول والثاني لاختبارات المراجعة. The study aims to determine the effect of the inevitable risk assessment on audit tests. For this purpose, the Researcher has done a field survey by distributing a questionnaire on the sample of the auditors, with whom the researcher could communicate. 56 questionnaires have been distributed, and 34 questionnaires from which have been returned. The results of data analysis showed that, there is consensus on the existence of a positive, extrusive effect of the inevitable risk assessment on the audit tests. And based on the results of the factorial analysis, the results showed that the inevitable risk could be divided into three factors and the audit tests into two factors, by which we are able to study the assessment effect for each factor of the inevitable risk on the components of the audit tests. Also, The results showed that the assessment of the first factor of the inevitable risk affects positively on the first factor of the audit tests, while has no effect on the second factor of the audit tests. But, for the second factor of the inevitable risk has been showed that, its assessment affects positively on the first factor of the audit tests, while has no effect on the second factor of the audit tests. Finally, the results showed that the assessment of the third factor of the inevitable risk has a reverse effect on both the first and the second factors of the audit tests.